Voyage of the Dawn Treader, the (The Chronicles of Narnia, Book 5) - Lewis, C. S. (HarperCollins Publishers London, 2009)
Illustrations in this ebook appear in vibrant full colour on a full colour ebook device, and in rich black and white on all other devices. Narnia ... where a dragon awakens ... where stars walk the earth ... where anything can happen. A king and some unexpected companions embark on a voyage that will take them beyond all known lands. As they sail farther and farther from charted waters, they discover that their quest is more than they imagined and that the world's end is only the beginning. The Voyage of the Dawn Treader is the fifth book in C.S. Lewis's The Chronicles of Narnia, a series that has become part of the canon of classic literature, drawing readers of all ages into a magical land with unforgettable characters for over fifty years. This is a novel that stands on its own, but if you would like to continue to the journey, read The Silver Chair, the sixth book in The Chronicles of Narnia